Penerapan Nilai-Nilai Serviam di Sekolah Ursulin Jenjang SMP: Penerapan Nilai-Nilai Serviam di Sekolah Ursulin Jenjang SMP - Tuba, Elisabeth; Mohammad Ali (Unika Santu Paulus Ruteng, 2023)
Integrative education which is not only oriented towards educating the nation's children intellectually, but also spiritually, socially-emotionally and kinesthetically, must be the concern of all education stakeholders. This is also a concern of educational stakeholders in Ursuline schools. Ursuline schools have main values or core values, namely Serviam which means